Role of Kupffer cells in acute hemorrhagic necrotizing pancreatitis-associated lung injury of rats - Liu, Hong-Bin; Cui, Nai-Qiang; Li, Dong-Hua; Chen, Chang (World journal of gastroenterology : WJG, 2006)
AIM： To investigate the role of Kupffer cells （KCs） in acute hemorrhagic necrotizing pancreatitis-associated lung injury （AHNP-U）. METHODS： Forty-two rats were allocated to four groups [sham operation, AHNP model, gadolinium chloride （GdCl3） pretreatment, GdCl3 control]. In GdCl3 pretreatment group, GdCl3 was administered by caudal vein injection 24 h before the AHNP model induction. Blood from the iliac artery, alveolar macrophages and tissues from the pancreas and lung, were collected in six animals per group 3 and 6 h after acute pancreatitis induction. TNF-α, IL-1 of Lserum, myeloperoxidase （MPO） of lung tissue, NF-κB activation of alveolar macrophages were detected. Serum AST and ALT in sham operation group and GdCl3 control group were tested. In addition, histopathological changes of the pancreas and lung were observed under light microscope. RESULTS： MPO of lung tissue and TNF-α, IL-1 levels of serum were all reduced significantly in GdCl3 pretreatment group compared to those in AHNP group （P〈0.01）. NF-KB activation of alveolar macrophages was also attenuated significantly in GdCl3 pretreatment group compared to that in AHNP group （P〈0.01）. The pathological injury of the lung was ameliorated obviously in GdCl3 pretreatment group compared to that in AHNP group. Nevertheless, the serum amylase level did not reduce and injury of the pancreas was not prevented in GdCl3 pretreatment group. CONCLUSION： Pulmonary injury induced by AHNP is mediated by KC activation and AHNP-LI can be significantly ameliorated by pretreatment with GdCh and KCs play a vital role in AHNP-LI.